The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1128/aac.01714-17
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Principle Study in a Murine Lung Infection Model of Antipseudomonal Activity of Phage PEV20 in a Dry-Powder Formulation

Abstract: Bacteriophage therapy is a promising alternative treatment to antibiotics, as it has been documented to be efficacious against multidrug-resistant bacteria with minimal side effects. Several groups have demonstrated the efficacy of phage suspension to treat lung infections using intranasal delivery; however, phage dry-powder administration to the lungs has not yet been explored. Powder formulations provide potential advantages over a liquid formulation, including easy storage, transport, and administration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 25 publications
0
62
0
Order By: Relevance
“…Lactose monohydrate (DFE Pharma, Goch, Germany) and L‐leucine (Sigma‐Aldrich, NSW, Australia) were used as excipients for spray drying PEV20. These two excipients can protect and stabilize phage particles from the stresses of spray drying with minimal titer loss, and form partially‐crystalline and partially‐amorphous particles 1,7 . Furthermore, our recent long‐term stability study has shown that lactose, despite being a reducing sugar, provides superior phage protection to trehalose 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactose monohydrate (DFE Pharma, Goch, Germany) and L‐leucine (Sigma‐Aldrich, NSW, Australia) were used as excipients for spray drying PEV20. These two excipients can protect and stabilize phage particles from the stresses of spray drying with minimal titer loss, and form partially‐crystalline and partially‐amorphous particles 1,7 . Furthermore, our recent long‐term stability study has shown that lactose, despite being a reducing sugar, provides superior phage protection to trehalose 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Delivering them as aerosols can achieve direct targeting in the lungs. The feasibility of bioengineering phages into inhalable powders by spray drying has been demonstrated in vitro 1‐6 along with efficacy studies in vivo 7,8 . In the production process, it is essential to preserve phage bioactivity in the dry state by suitable excipients.…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide strong support for inhaled phage therapy with reduction in bacterial load and inflammation in the mouse lung infection model. Compared with intranasal route, intratracheal administration enables direct application of bacteria and phages to the mouse lungs with minimal loss in other parts of the respiratory route, including nose, throat and upper airways (8,27). Hence, the exact phage doses of interest were given in the PK study, and in the PD study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages, studies on intratracheal administration of phages for lung infections have been scarce (8,28). In this study, intratracheal instillation was used to administer and assess the PK of phage PEV31 at two different doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation